Leveraging microbicidal and immunosuppressive potential of herbal medicine in oral diseases - Banks, Jonathan M.; Brandini, Daniela A. [UNESP]; Barbosa, Debora B. [UNESP]; Takamiya, Aline S. [UNESP]; Thakkar, Pari; Zheng, Kathy; Naqvi, Afsar R. (Elsevier, 2022)
For thousands of years, humans have benefitted from the medicinal properties of plants and their derivatives. The anti-inflammatory, pain relieving, and anti-microbial properties present in plants and their extracts have been used in valuable therapies to treat diseases, bring comfort, and improve health. Plant-based therapies have shown promising outcomes in treating oral diseases. Oral infections caused by pathogens, such as caries and periodontitis, are chronic and widespread diseases that affect human health globally. However, these diseases involve similar biological pathways and immune responses that other diseases around the body share, including diseases that plant compounds are known to treat. In this chapter, we explore the developing and exciting field of plant-based medicine in the treatment of oral diseases.
Keywords: Dental caries; Gingivitis; Herbal medicine; Immune response; Oral pathology; Periodontitis; Wound healing